Efficient and stable titania-based nanocatalytic materials for the reductive amination of furfural. (June 2022) - Ronda-Leal, M.; Espro, C.; Lazaro, N.; Selva, M.; Perosa, A.; Osman, S.M.; Pineda, A.; Luque, R.; Rodríguez-Padrón, D.
Abstract: Highly active, selective and stable titania-based catalytic materials have been designed through a simple and environmentally friendly microwave-assisted approach. Further modification of the prepared titania with metal nanoparticles was carried out by a simple chemical reduction method. The synthesized materials displayed excellent catalytic behaviour in the reductive amination of furfural towards furfuryl amine. More importantly, the materials showed remarkable recyclability, retaining high conversion and selectivity values after six reaction cycles. Highlights: Reductive amination reaction of furfural. Supported Rh vs Ru nanoparticles as highly active systems. Metals having a drastic influence into the activity and selectivity of the reaction.